Camel mastitis in Southern Algeria - Saidi, Radhwane (Array, 2021)
In Algeria, camel breeding participates in the national milk production. However, this breeding faces significant health problems, including mammary pathologies. This disease is a major public health threat, due to the existence of human pathogens in milk. Several species are associated with this mastitis. Unlike cow"s milk, goat and camel milk are most often consumed in the fresh raw state, thus escaping any official control. The present study aimed to determine the nature and frequency of mastitis, and the nature and frequency of the responsible bacteria in each type of mastitis in southern Algeria. A total of 62 camels were subjected to clinical examination and screening for subclinical mastitis and the presence of Brucella using the California Mastitis Test (CMT) and ring test, respectively. CMT positive samples were then further subjected to bacteriological analysis. Clinical and subclinical mastitis were present with frequencies of 4.44% and 95.55%, respectively. Bacteriological analysis isolated a total of 73 samples of 45 seeds. Staphylococci were most commonly isolated, with a frequency of 63.01%. Among these, Staphylococcus aureus were at the top of the list, with 35.61%, while Staphylococcus SCN (coagulase negative staphylococci) represented only 27.39%. Streptococci were the second most isolated group, with 28.77%. Gram-positive bacilli were in third place, accounting for 6.85% of all isolates. Gram- negative bacilli (enterobacteria) were isolated with a frequency of 1.36%. Brucella was present with a frequency of 4.44%. Finally, an extended study on a larger sample of camels is required in the future.